Responsibility Of The Office Of The Land Act Maker (PPAT) Towards The Land Sale And Purchase Act Made In The Case Of Data False By The Parties - Yoga Ekasaputra Kuswandi (Sultan Agung Notary Law Review, 2020)
This study aims to analyze the responsibilities of the Land Deed Making Officer (PPAT) on the land sale and purchase deed made in the event that there is falsified data by the parties and the legal consequences of the land sale and purchase deed that contains falsified data. This study is a normative law study that departs from the emptiness of norms on legal protection for Land Deed Making Officials (PPAT) on information, identity, and or false documents submitted by the parties that are used as the basis for making a deed of sale. This study uses a legal approach, a conceptual approach, and a case approach. The legal materials used in this research are primary legal materials and secondary legal materials. The technique of collecting legal materials used is a literature study. The theories used in this research are the Theory of Legal Certainty and the Theory of Legal Authority. The results of this study show that the responsibility of the Land Deed Making Officer (PPAT) for false information, identity, and or documents in the making of the deed of the parties/parties of the deed cannot be held accountable by the Land Deed Making Officer (PPAT) as long as the Land Deed Making Officer (PPAT) does not violates the Law and Regulations of the Department of Land Deed Making Officials (PPAT), does not violate the technique of making deeds or applicable laws and regulations. Consequences of law Against land sale and purchase deeds that contain data that was falsified by the parties and known at the time of applying for a certificate of title, the land sale and purchase deed that has been made that contains data that was falsified by the parties, then the act is legally defective or invalid legally or legally void. Advice to the Land Deed Making Officer (PPAT): The Land Deed Making Officer (PPAT) to always try to be professional and when called the investigator remains silent and states that he is using his right to default.